2016
DOI: 10.1097/mpa.0000000000000435
|View full text |Cite
|
Sign up to set email alerts
|

Cartilage Oligomeric Matrix Protein-Angiopoietin-1 Has a Protective Effect of Vascular Endothelial Barrier in Rat With Acute Necrotizing Pancreatitis

Abstract: COMP-Ang-1 can upregulate the expression of Ang-1 protein to promote angiogenesis and improve early inflammatory and pathological damage in ANP group.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
2
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 19 publications
1
2
0
Order By: Relevance
“…These results showed that DCQD could effectively alleviate the capillary leakage and the damage to the endothelial barrier function due to the inflammatory reaction process via regulation of the endothelial barrier-related proteins. The results were consistent with the results of our previous study [9, 26]. …”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…These results showed that DCQD could effectively alleviate the capillary leakage and the damage to the endothelial barrier function due to the inflammatory reaction process via regulation of the endothelial barrier-related proteins. The results were consistent with the results of our previous study [9, 26]. …”
Section: Discussionsupporting
confidence: 83%
“…It can also regulate the proliferation of endothelial cells and vascular smooth muscle cells to promote the maturation of blood vessels, which is very important for maintaining the stability and integrity of blood vessels [23-25]. Our previous studies found that serum Ang-1 levels in AP rats are significantly decreased, and after treatment with Ang-1, the amounts of inflammatory factors in serum dramatically decline and the capillary permeability of tissue decreases [26]. Therefore, this experiment used Ang-1 in the positive control group.…”
Section: Discussionmentioning
confidence: 99%
“…In support of this hypothesis, a limited number of mainly in vivo studies have previously reported the ability of COMP-Ang1 to improve microvascular function. Cho et al11 showed that COMP-Ang1 can promote wound healing through enhancement of angiogenesis and blood flow in diabetic db/db mice, whereas Chen et al12 demonstrated that COMP-Ang1 can protect endothelial barriers in rats with acute necrotizing pancreatitis. Subretinal and intravitreal delivery of COMP-Ang1 cloned into an adeno-associated virus vector (AAV2.COMP-Ang1) exhibited microvasculature-related improvements in mouse models of AMD13 and diabetic retinopathy,14 respectively.…”
mentioning
confidence: 99%